AN ERROR ANALYSIS OF ENGLISH MONOPHTHONG PRONUNCIATION AMONG FOURTH SEMESTER STUDENTS IN AN ENGLISH EDUCATION PROGRAM - Alya Putri, Rahma; Kusrin; Wachyudi, Kelik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pronunciation has a central place in oral communication because listeners do not only hear words, they also interpret meaning through the clarity of sounds. Many learners of English as a foreign language still find English vowels difficult to produce, especially monophthongs that are not clearly represented in the Indonesian vowel system. This study aimed to identify the types of errors found in students’ pronunciation of English monophthongs, to determine the vowel sounds that were most frequently mispronounced, and to examine the possible sources of those errors. The study used a basic qualitative design supported by simple frequency counts. The participants were 15 fourth semester students in an English Language Education Program at a university in Karawang who had completed a Phonetics and Phonology course. Data were gathered through a pronunciation test and semi structured interviews. The pronunciation data were transcribed with the International Phonetic Alphabet and then classified by using the surface strategy taxonomy. The findings showed 144 pronunciation errors. Misformation, understood in this study as vowel substitution, appeared 143 times or 99.3 percent, while omission appeared only once or 0.7 percent. The monophthongs most often mispronounced were /ɔː/ at 25.7%, /æ/ at 24.3%, /uː/ at 23.6%, and /iː/ at 11.8%. The interviews suggested that interlingual transfer and intralingual transfer were the most visible sources of error, while learning context and communication strategies also shaped the students’ pronunciation in smaller ways. The study indicates that differences between Indonesian and English vowel systems, particularly vowel quality and vowel length, still create considerable difficulty for university EFL learners.